Passive Range of Motion Intervention to Improve Physical Mobility in a Hemorrhagic Stroke Patient After External Ventricular Drainage: A Case Study - Siti Komariah; Tentry Fuji Purwanti; Budi Rustandi; Lisbet Octovia Manalu (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2026)
Background: Hemorrhagic stroke is a life-threatening neurological disorder that often leads to significant motor impairment due to intracranial bleeding, elevated intracranial pressure, and disrupted neuromuscular function. Patients in intensive care settings are highly susceptible to complications related to prolonged immobility, including joint stiffness, muscle weakness, atrophy, contractures, impaired circulation, and pressure injuries. Passive Range of Motion (ROM) exercises are commonly applied as a nursing intervention for patients who are unable to perform voluntary movement, aiming to preserve joint mobility and prevent musculoskeletal deterioration. Objective: This case study aimed to describe the implementation of nursing care in a hemorrhagic stroke patient with impaired physical mobility following External Ventricular Drainage (EVD), with a focus on the application and evaluation of passive ROM exercises in the General Intensive Care Unit (GICU). Methods: A descriptive case study design was employed involving a female patient with hemorrhagic stroke who underwent EVD placement. Data were collected through comprehensive nursing assessment, direct observation, interviews, and medical record review. Passive ROM exercises were administered twice daily for 10–15 minutes using controlled movements of the upper and lower extremities. Neurological status, hemodynamic stability, and EVD function were continuously monitored. Results: Over a five-day period, gradual improvement was observed. Muscle strength increased by one grade, joint mobility improved by approximately 10 degrees, and the Glasgow Coma Scale reached 12. No complications related to the intervention or EVD were identified. Conclusion: Passive ROM may be safely incorporated into nursing care for hemorrhagic stroke patients with EVD and may help maintain joint function and reduce immobility-related complications, although outcomes are influenced by multiple clinical factors.